Quantitative impacts of climate change and human activities on grassland growth in Xinjiang, China - Rui, Hanyi; Luo, Beier; Wang, Ying; Zhu, Lin; Zhu, Qinyuan (Frontiers in Plant Science, 2025)
Grassland is an important vegetation type in Xinjiang, China, playing a crucial role in the terrestrial carbon cycle. Previous studies have shown that both climate change and human activities significantly impact grassland growth. However, research quantifying the contributions of these two factors to grassland changes is still not thorough enough. This study utilized remote sensing data, i.e., Normalized Difference Vegetation Index (NDVI), to analyze the spatial trends of grassland changes from 1982 to 2015, and the correlation between NDVI and climate factors. Then, relative contributions of climate change and human activities to grassland changes were explored across Xinjiang. The results indicated that there was a significant spatial heterogeneity in the interannual variations of NDVI in the study area, showing an overall increasing trend (covering 62.5% of the study area). This was mainly attributed to the warming and humidifying trend of Xinjiang’s climate in recent decades, where increased precipitation and rising temperatures promoted grassland growth. The main regions with increased NDVI included the western part of Changji Hui Autonomous Prefecture, the southern part of Tacheng Prefecture, and the northwestern part of the Tarim Basin; while the areas with decreased NDVI were mainly located in the western part of the study area, e.g., the Ili River basin, and the Tekes River basin. Compared to precipitation, NDVI showed a stronger correlation with temperature, which was related to temperature promoting organic matter decomposition and enhancing vegetation nutrient utilization efficiency. NDVI was negatively correlated with VPD, mainly due to the effects of transpiration and surface evaporation. In terms of grassland growth, climate change (52%) contributed as much as human activity (48%). For the grassland reduction, human activities played a larger role. Overall, in mountainous and flat areas, human activities contributed more (64.29%) than climate change (35.71%), including activities such as grazing and urbanization.